Physicochemical and elemental analyses of sandstone quarrying wastes to assess their impact on soil properties. (1st October 2020) - Singhal, Abhishek; Goel, Sudha; Sengupta, Debashish
Abstract: The use of sandstone as a building material has increased around the world and sandstone quarrying and its wastes pose a potential threat to human health and the environment. More than 50% of the excavated stone is wasted in the form of scrap stone and waste slurry during sandstone quarrying and processing. Sandstone wastes can adversely change native soil properties and should be reused as construction material. The present study aimed to characterise wastes generated during sandstone quarrying and processing, assess their impact on the soil environment and explore their reuse potential. The results of this study show that fine slurry waste has physicochemical properties between sand and sandy loam while the properties of the slurry solids and scrap stone are similar to those of sandstone. Fine stone waste on intrusion into soil reduced the hydraulic conductivity and porosity of soil potentially reducing its productivity. The liquid stone slurry contained metals like Mn, Ni and As at concentrations higher than drinking water standards. These metals may contaminate water sources and affect human health. Therefore, the use of stone wastes as aggregate for road and building construction would be beneficial and would reduce their adverse impacts on the environment. Graphical abstract: Image 1 Highlights: Large amounts of sandstone waste are generated in the stone quarries of Rajasthan. Ten soil samples from quarry site and six background soil samples were analysed. Sandstone quarrying can alter soil properties in an adverse way. Stone waste dust intrusion can reduce soil porosity and hydraulic conductivity. Stone waste can be used in construction of roads or as landfill cover material.